2020
DOI: 10.1111/are.15060
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal microbial profiling of left kidney and stomach of farmed adult greenlip abalone ( Haliotis laevigata )

Abstract: As sequencing and data analysis methods improve and more bacterial species are identified, microbial profiling has been performed more widely in marine species. To enable the development of potential prophylactic strategies against bacterial disease in abalone induced by elevated water temperatures, the left kidney and stomach samples of six unaffected adult greenlip abalone Haliotis laevigata were sampled in summer and winter to enable comparisons of endogenous abalone microbial profiles. Under the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
2
2
0
Order By: Relevance
“…High-throughput sequencing technology can better visualize the microbial communities associated with abalone farming. Results showed that Proteobacteria and Bacteroidetes are the dominant bacteria and most efficient colonizers in abalone farming waters, which is consistent with previous studies [27]. In…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High-throughput sequencing technology can better visualize the microbial communities associated with abalone farming. Results showed that Proteobacteria and Bacteroidetes are the dominant bacteria and most efficient colonizers in abalone farming waters, which is consistent with previous studies [27]. In…”
Section: Discussionsupporting
confidence: 92%
“…High-throughput sequencing technology can better visualize the microbial communities associated with abalone farming. Results showed that Proteobacteria and Bacteroidetes are the dominant bacteria and most efficient colonizers in abalone farming waters, which is consistent with previous studies [27]. In contrast to terrestrial animals, microorganisms in the aquatic environment have a significant impact on the bacterial composition of aquatic animals due to their constant contact with the surrounding aquatic environment [28][29][30].…”
Section: Discussionsupporting
confidence: 91%
“…1B ). Meanwhile, previous studies on gastrointestinal bacterial communities from abalones with different species ( 3 , 9 11 , 24 ), geographical locations ( 3 , 9 , 10 , 24 , 25 ), and diets ( 3 , 11 , 24 ) also support that Psychrilyobacter is a core predominant member, even reaching over 90% in some species, such as H. tuberculate ( 3 ).…”
Section: Resultsmentioning
confidence: 84%
“…1B). Meanwhile, previous studies on gastrointestinal bacterial communities from abalones with different species (3,(9)(10)(11)24), geographical locations (3,9,10,24,25) and diets (3,11,24) also support that Psychrilyobacter is a core predominant member, even reaching over 90% in some species, such as Haliotis tuberculate (3).…”
Section: Psychrilyobacter Dominated the Abalone Gut And Was Widely Di...mentioning
confidence: 91%